Urban Sprawl and Northern European Residential Tourism in the Spanish Mediterranean Coast - Joan Carles Membrado; Raquel Huete; Alejandro Mantecón (Via@)
Residential tourism from Northern European countries has influenced the process of urban development in the Spanish Mediterranean coast. We explain the recent urban growth in Spain (or “Spanish house bubble”) and then show the main characteristics of the influx of citizens from other European countries richer than Spain, especially into the Spanish Mediterranean coast and specifically into the Costa Blanca region. Finally we demonstrate the relationship between the development of residential tourism and the growth of urban sprawl in the Spanish Mediterranean coast and we analyze some of its consequences for the region..